As virtudes medicinais do tabaco, a ‘erva santa’, descritas por um missionário europeu no Oriente (c. século XVI) - Viotti, Ana Carolina De Carvalho [UNESP] (MCTI/Museu Paraense Emílio Goeldi, 2020)
Probably in the mid-16th century, a European religious named Leonel de Sousa, on a mission to the easternmost parts of the known world, recorded in a ten-folio manuscript, the “Vertude da Erva Sancta que he o tabaco” (n.d.). There, he has revealed the most prominent uses of these American plant, such as diseases for which it was useful and the most accurate ways to handle and extract the potential healing components of the natural element. The herb he referred to as ‘holy’, the tobacco, was not unequivocally seen as so, especially among other priests or religious men who in diverse writings, underlines the addiction that could be aroused by its consumption. This characteristic makes the compilation worthy of a more thorough analysis. It is to the full transcription of this manuscript, with brief comments and indications, that this text is dedicated.

Provavelmente em meados do século XVI, um religioso europeu de nome Leonel de Sousa, em missão às partes mais a leste do mundo conhecido, registrou, em um manuscrito de dez fólios, a “Vertude da Erva Sancta que he o tabaco” (n.d.). Ali, anotou os mais destacados usos da planta americana, as doenças para as quais seria útil e as formas mais precisas de manusear o elemento e extrair dele seu potencial curativo. A erva a que se refere, o tabaco, não gozava do predicado de ‘santa’ inequivocamente, sobretudo entre outros homens de fé que, em escritos diversos, sublinharam os vícios despertados por seu consumo, o que torna a compilação merecedora de uma análise mais detida. É à transcrição integral deste manuscrito, acrescida de breves comentários e indicações, que este texto se dedica.
The medical virtues of tobacco, the ‘holy herb’, described by a European missionary in the East (c. 16th century)
Keywords: Tobacco; Plants; Medicine; Health; East; Tabaco; Plantas; Medicina; Saúde; Oriente